Pipelines 2021 Construction and Rehabilitation - Strayer, Duane; Jenkins, C. Douglas (American Society of Civil Engineers, 2021)
Papers from sessions of Pipelines 2021, held virtually August 3-6, 2021. Sponsored by the Utility Engineering and Surveying Institute of ASCE.This collection contains 51 peer-reviewed papers on the construction and rehabilitation of pipelines.Topics include: trenchless applications; sewer construction and rehabilitation; testing and commissioning; watermain construction and rehabilitation; and case studies.This collection will be of interest to design and consulting engineers, utility and pipeline owners, and researchers in the pipeline profession.
Keywords: Construction projects -- Management.; Pipelines -- Design and construction -- Congresses.; elektronické knihy; electronic books